Let $a_1,a_2,\ldots ,a_n$, be positive real numbers and S = $a_1+a_2+a_3+\cdots+a_n$. Use the Cauchy-Schwarz inequality to prove that

$$\sum_{i=1}^{i=n}\frac{a_i}{S-a_i}\geqslant \frac{n}{n-1}$$ and $$\sum_{i=1}^{i=n}\frac{S-a_i}{a_i}\geqslant n(n-1)$$

Hint: Apply the inequality to:

  • $\sum \frac{S}{a_i}$ and $\sum \frac{a_i}{S}$ for one case,
  • and $\sum a_i(S-a_i)$ and $\sum \frac{a_i}{S-a_i}$ for the other case.
  • 2
    $\begingroup$ Have you written down the version of Cauchy-Schwarz you want to use? If not, do it! $\endgroup$ – martini Mar 27 '12 at 10:08
  • 3
    $\begingroup$ I think the hint says clearly what you have to do. You only need to write the corresponding Cauchy Schwarz inequality and you are done. $\endgroup$ – Beni Bogosel Mar 27 '12 at 10:17

Cauchy Schwarz Inequality:

$$ \begin{align*} \left( \frac{1}{a_1}+\frac{1}{a_2}+\dots +\frac{1}{a_n}\right)\left( a_1+a_2+\dots+a_n \right) &\geq \left(\frac{1}{\sqrt{a_1}}\sqrt{a_1}+\frac{1}{\sqrt{a_2}}\sqrt{a_2}+\dots +\frac{1}{\sqrt{a_n}}\sqrt{a_n} \right)^2 \\\ &\geq \left( 1+1+\dots+1\right)^2 = n^2 \end{align*} $$

which when applied here $$ \begin{align*} \displaystyle\sum_{i=1}^n \frac{S}{a_i} &= \left( \frac{1}{a_1}+\frac{1}{a_2}+\dots +\frac{1}{a_n}\right)S \geq n^2\\ \end{align*} $$

Therefore $$ \begin{align*} \displaystyle\sum_{i=1}^n \frac{S-a_i}{a_i} &= \displaystyle\sum_{i=1}^n \frac{S}{a_i} -n\\ &\geq n^2 - n = n(n-1) \tag{1} \end{align*} $$

Similarly, re-writing the other summation

$$ \begin{align*} \displaystyle\sum_{i=1}^n \frac{a_i}{S-a_i} &= \frac{S-\displaystyle\sum_{j \neq 1}a_j}{\displaystyle\sum_{j \neq 1}a_j} + \frac{S-\displaystyle\sum_{j \neq 2}a_j}{\displaystyle\sum_{j \neq 2}a_j}+\dots +\frac{S-\displaystyle\sum_{j \neq n}a_j}{\displaystyle\sum_{j \neq n}a_j}\\ &= \displaystyle\sum_{i=1}^n \left(\frac{S}{\displaystyle\sum_{j \neq i}a_j}\right)-n \tag{2} \end{align*} $$

Also since

$$ \displaystyle\sum_{j \neq 1}a_j+\displaystyle\sum_{j \neq 2}a_j+\dots+\displaystyle\sum_{j \neq n}a_j = (n-1)S $$

By Cauchy-Schwarz Inequality $$ \begin{align*} \displaystyle\sum_{i=1}^n \left(\frac{1}{\displaystyle\sum_{j \neq i}a_j}\right)(n-1)S \geq n^2\\ \Longrightarrow \displaystyle\sum_{i=1}^n \left(\frac{1}{\displaystyle\sum_{j \neq i}a_j}\right) \geq \frac{n^2}{(n-1)S} \end{align*} $$

From $(2)$

$$ \begin{align*} \displaystyle\sum_{i=1}^n \frac{a_i}{S-a_i} &\geq \left(\frac{n^2}{n-1}\right) - n\\ &\geq \frac{n}{n-1} \end{align*} $$


The left sides are the values of $\sum f(p_i)$ and $\sum g(p_i)$ with $\sum p_i = 1$ being constant, where

$f(x) = \dfrac{x} {1-x}$ $g(x) = \dfrac 1 x - 1$, and $p_i = \dfrac {a_i} S $.

Both functions are convex for $x>0$, so that each sum of values is minimized when all arguments $p_i$ (and therefore all $a_i$) are equal.

Another line of argument that makes this obvious is the Rearrangement Inequality: the average of the sequence $x_i y_i$ is larger or equal to the product of the averages of $x_i$ and $y_i$ if the two sequences are in the same order. In the first inequality the sequences $a_i$ and $(S-a_i)^{-1}$ are in the same order, and in the second inequality, $(S-a_i)$ and $1/a_i$ are in the same order. The averages of $a_i$ and $(S-a_i)$ are $S/n$ and $(n-1)S/n$, which depend only on $S$. The other averages lead to the standard problem of minimizing a sum of reciprocals given the sum of the variables, which happens when the summands are equal.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.